Computer utterances: Sequence and event in digital architecture. (December 2017) - Miranda, Pablo
Barely a month before the end of World War II, a technical report begun circulating among allied scientists: the 'First Draft of a Report on the EDVAC', attributed to John von Neumann, described for the first time the design and implementation of the earliest stored-program computer. The 'First Draft' became the template followed by subsequent British and American computers, establishing the standard characteristics of most computing machines to date. This article looks at how the material and design choices described in this report influenced architecture, as it set up the technological matrix onto which a discipline relying on a tradition of drawn geometry would be eventually completely remediated. It consists of two parts: first, a theoretical section, analysing the repercussions for architecture of the type of computer laid out in the 'First Draft'. Second, a description of a design experiment, a sort of information furniture, that tests and exemplifies some of the observations from the first section. This experiment examines the possibilities of an architecture that, moving beyond geometric representations, uses instead the programming of events as its rationale. The structure of this article reflects a methodology in which theoretical formulation and design experiments proceed in parallel. The theoretical investigation proposes concepts that can be tested and refined through design and conversely design work determines and encourages technical, critical and historical research. This relation is dialogical: theoretical investigation is not simply a rationalisation and explanation of earlier design work; inversely, the role of design is not just to illustrate previously formulated concepts. Both design and theorisation are interdependent but autonomous in their parallel development.